Ukraine: ‘Callous disregard for human life’ of Russian forces’ response to Kakhovka dam destruction compounded by its disastrous effects upstream - Amnesty International (Amnesty International, 2023)
As the consequences of the Kakhovka dam destruction continue to unfold, the occupying Russian forces have been endangering lives in flood-afflicted areas following the destruction of the dam, while upstream water shortages and an upheaval of livelihoods point to an impending ecological and economic disaster, Amnesty International said today.
Ukraine
Keywords: 2023-06 June

Tunisia: Human rights at risk two years after President Saied’s power grab - Amnesty International (Amnesty International, 2023)
In the second year since Tunisian President Kais Saied’s power grab, Tunisian authorities have taken further steps towards repression by jailing dozens of political opponents and state critics, violated the independence of the judiciary, dismantled institutional human rights safeguards, and incited discrimination against migrants, Amnesty International said today. “Decree by decree, blow by blow, President Saied and his government have dramatically undermined respect for human rights in Tunisia since his power grab in July 2021. In doing so, he has stripped away basic freedoms that Tunisians fought hard to earn and fostered a climate of repression and impunity. The Tunisian authorities must immediately reverse this treacherous trajectory and uphold their international human rights obligations,” said Heba Morayef, Amnesty International’s Regional Director for the Middle East and North Africa.
Tunisia
Keywords: 2023-07 July; Kaïs Saïed

Zimbabwe: Acquittal of imprisoned opposition leader shows growing cases of misuse of justice system to target critical voices - Amnesty International (Amnesty International, 2023)
Responding to yesterday’s High Court acquittal of opposition leader, Jacob Ngarivhume, who was sentenced in April to 48 months imprisonment for leading protests against government corruption, Khanyo Farisè, Amnesty International’s Deputy Director for Southern Africa, said: “His imprisonment is a travesty, and an affront to Zimbabwe’s constitution and the country’s international human rights obligations. No […]
Zimbabwe
Keywords: 2023-12 December

Amnesty petition demanding ceasefire in Gaza, Israel backed by over million signatures - Amnesty International (Amnesty International, 2023)
The world is watching in horror as more and more civilians lose their lives each day amid Israel’s relentless bombardment and ground operations.
Israel
Keywords: 2023-10 November

Security forces used rape and other sexual violence to crush “Woman Life Freedom" uprising with impunity - Amnesty International (Amnesty International, 2023)
A report demonstrates that security forces in Iran used rape and other forms of sexual violence, amounting to torture and other ill-treatment, to intimidate and punish peaceful protesters during the 2022 “Woman Life Freedom” uprising.
Iran, Islamic Republic of
Keywords: 2023-12 December

Mexico is criminalizing land, territory and environmental defenders - Amnesty International (Amnesty International, 2023)
The disproportionate use of criminal law is one of the main threats facing the right to protest peacefully in defense of land, territory and environment in Mexico, Amnesty International said today upon publishing a new report. Mexico: Land and Freedom? Criminalizing defenders of land, territory and environment documents the disproportionate use of the justice system to deter, punish and prevent defenders from protesting in demand of their rights.
Mexico
Keywords: 2023-09 September; Chilón; Colonia Maya; Land Defenders; Sitilpech; Zacatepec

Cambodia: Mass evictions at UNESCO World Heritage site Angkor violate international law - Amnesty International (Amnesty International, 2023)
Cambodian authorities cruelly uprooted families who have lived in Angkor for several generations.
Cambodia
Keywords: 2023-10 November

Respect families’ right to commemorate loved ones killed during uprising without reprisals on one-year anniversary - Amnesty International (Amnesty International, 2023)
In new research, Amnesty International details how the Iranian authorities have been subjecting victims’ families to arbitrary arrest and detention, imposing cruel restrictions on peaceful gatherings at grave sites, and destroying victims’ gravestones.
Iran, Islamic Republic of
Keywords: 2023-08 August

Sudan: Neighbouring countries must provide safe passage to those fleeing conflict - Amnesty International (Amnesty International, 2023)
Between 9 May and 16 June, Amnesty International interviewed 29 civilians faced with the difficult choice of whether to return to the conflict they fled, or remain stranded at the border, where they may wait for an indefinite period without basic supplies to maintain their health, privacy, and dignity.
Sudan
Keywords: 2023-07 July

Ukraine: Russian court upholds 13-year sentence against Ukrainian human rights defender Maksym Butkevych - Amnesty International (Amnesty International, 2023)
An appeal hearing at a Moscow court on Tuesday (22 August) which has upheld the 13-year sentence imposed on Maksym Butkevych, a Ukrainian human rights defender, is a grave miscarriage of justice Amnesty International said today.
Ukraine
Keywords: 2023-08 August; Russia

Migrants’ rights defender from Russia convicted solely for her human rights work - Amnesty International (Amnesty International, 2023)
Tatyana Kotlyar is being punished simply for helping hundreds of people, including migrants and refugees, by generously registering them at her home.
Russian Federation
Keywords: 2023-06 June

Iran: International community must stand with women and girls suffering intensifying oppression - Amnesty International (Amnesty International, 2023)
The Iranian authorities are doubling down on their oppressive methods of policing and severely oppressing Iranian women and girls for defying degrading compulsory veiling laws, Amnesty International said today. In a detailed analysis published today, the organization exposes the authorities’ intensified nationwide crackdown on women and girls who choose not to wear headscarves in public.
Iran, Islamic Republic of
Keywords: 2023-07 July

Arbitrary detentions continue in Venezuela - Amnesty International (Amnesty International, 2023)
Venezuela: Arbitrary detentions continue as a tool of government control and repression. In the new report, Life detained: Politically motivated arbitrary detentions continue in Venezuela Amnesty International denounces the Nicolás Maduro.
Venezuela, Bolivarian Republic of
Keywords: 2023-08 August

Viet Nam: Drop charges and immediately release activist sentenced to six years in prison - Amnesty International (Amnesty International, 2023)
“The unfair charges and inhumane prison conditions shows the Vietnamese authorities’ willingness to systematically silence dissent in direct violation of international human rights law."
Viet Nam
Keywords: 2023-07 July

Countries must safeguard children’s rights from climate change and environmental damage - UN committee - Amnesty International (Amnesty International, 2023)
UN Committee on the Rights of the Child has concluded that countries must urgently implement measures to address the damage and threat to children’s rights from climate change and environmental degradation.
Worldwide
Keywords: 2023-08 August; Child Rights

Amnesty petition demanding ceasefire in Gaza, Israel backed by over million signatures - Amnesty International (Amnesty International, 2023)
The world is watching in horror as more and more civilians lose their lives each day amid Israel’s relentless bombardment and ground operations.
Palestine (permanent observer to the UN)
Keywords: 2023-10 November

Malta: Lives put at risk as parliament waters down bill seeking to partially decriminalize abortion - Amnesty International (Amnesty International, 2023)
The Maltese authorities’ decision to water down a version of a bill aimed at partially decriminalizing abortion in cases of grave risk to the life or health of pregnant people will endanger lives, Amnesty International said following the bills’ adoption by parliament.
Malta
Keywords: 2023-06 June

Burundi: Amend gender-based violence law - Amnesty International (Amnesty International, 2023)
Burundi’s 2016 law against gender-based violence was a milestone achievement, bringing improved protection. However, it falls short of regional and international best practice, and in some instances undermines rather reinforces the fight against gender-based violence. This briefing proposes how to strengthen protections, including through revisions of the law.
Burundi
Keywords: 2023-12 December

Israeli attacks wipe out entire families in Gaza - Amnesty International (Amnesty International, 2023)
Amnesty International has documented damning evidence of war crimes.
Israel
Keywords: 2023-10 October; Palestine

Eswatini: Authorities must stop using the courts to intimidate and harass union leaders - Amnesty International (Amnesty International, 2023)
Ahead of the court appearance of Sticks Nkambule, Secretary General of Swaziland Transport Communication and Allied Workers Union, on trumped-up charges of contempt of court stemming from his involvement in organizing a stay away action in December 2022, Vongai Chikwanda, Amnesty International’s Interim Deputy Director for Southern Africa, said: The harassment and intimidation of Sticks Nkambule shows that Eswatini authorities are effectively criminalizing peaceful dissent.
Eswatini
Keywords: 2023-06 June

Lebanon: Comedian Arrested for Critical Jokes - Amnesty International (Amnesty International, 2023)
Lebanese authorities’ arrest and investigation of prominent comedian Nour Hajjar, solely in retaliation for his jokes, represents a new escalation in Lebanon’s crackdown on public criticism, the Coalition to Defend Freedom of Expression in Lebanon of which Amnesty International is a member, said today.
Lebanon
Keywords: 2023-08 August

Ugandan authorities must drop charges in death penalty case under Anti-Homosexuality Act - Amnesty International (Amnesty International, 2023)
It is deeply disturbing that the Ugandan authorities are prosecuting people based on their real or perceived sexual orientation or gender identity.
Uganda
Keywords: 2023-08 August

Social media companies must step up crisis response on Israel-Palestine as online hate and censorship proliferate - Amnesty International (Amnesty International, 2023)
Social media companies must urgently address the fanning of online hate and racism against Palestinian and Jewish communities, Amnesty International said as the conflict in Israel and the Occupied Palestinian Territories escalates further
Israel
Keywords: 2023-10 October; Palestine

“Death came to our home”. War crimes and civilian suffering in Sudan - Amnesty International (Amnesty International, 2023)
Sudan: War crimes rampant as civilians killed in both deliberate and indiscriminate attacks. Read the Report
Sudan
Keywords: 2023-08 August

EU: European Parliament adopts ban on facial recognition but leaves migrants, refugees and asylum seekers at risk - Amnesty International (Amnesty International, 2023)
EU: European Parliament adopts ban on facial recognition but leaves migrants, refugees and asylum seekers at risk. Responding to the European Parliament’s decision to ban invasive mass surveillance technologies in its Artificial Intelligence Act (AI Act), Mher Hakobyan, Advocacy Advisor on AI Regulation said: “We welcome the European Parliament’s decision to adopt a ban on abusive mass surveillance technology in today’s landmark vote. However, it is essential the Parliament and EU Member States ensure that development, sale, use and export of facial recognition and other mass surveillance technologies are banned in the final AI Act during upcoming negotiations.
Europe
Keywords: 2023-06 June

Russia: Investigate vicious attack on Elena Milashina and Aleksandr Nemov in Chechnya - Amnesty International (Amnesty International, 2023)
The vicious beating of Elena Milashina and Aleksandr Nemov by masked assailants in Chechnya this morning was an abhorrent act of violence that must not go unpunished
Russian Federation
Keywords: 2023-07 July; Chechnya; Tchétchénie

Biden and Modi must address grave human rights concerns - Amnesty International (Amnesty International, 2023)
The United States and Indian governments must address the grave human rights issues in both countries during Prime Minister Modi’s meeting with President Biden in Washington DC, said Amnesty International ahead of the state visit this week.
India
Keywords: 2023-06 June

‘Predator Files’ spyware scandal reveals brazen targeting of civil society, politicians and officials - Amnesty International (Amnesty International, 2023)
Shocking spyware attacks have been attempted against civil society, journalists, politicians and academics in the European Union (EU), USA and Asia, according to a major new investigation by Amnesty International.
Worldwide
Keywords: 2023-10 October

Stop harassing and arbitrarily arresting Afghans seeking refuge - Amnesty International (Amnesty International, 2023)
The situation of Afghan refugees in Pakistan is not receiving due international attention.
Pakistan
Keywords: 2023-06 June

Netherlands: 'Historic victory' as law amended to recognize that sex without consent is rape - Amnesty International (Amnesty International, 2023)
Responding to the news that the Netherlands’ House of Representatives has voted to amend the Sexual Offences Act by introducing a consent-based definition of rape.
Netherlands
Keywords: 2023-07 July

Saudi Arabia: Imminent execution of seven young men would violate kingdom’s promise to abolish death penalty for juveniles - Amnesty International (Amnesty International, 2023)
Despite the Saudi authorities’ commitment to end their use of the death penalty against children under 18 at the time of the crime, seven young men are at risk of imminent execution after an appeals court confirmed their punishment, Amnesty International said today. Their execution would mark a chilling escalation of the already record-breaking use of the death penalty with the number of executions in the country having increased seven-fold in the past three years alone. “Saudi authorities have promised to limit the use of the death penalty and adopted legal reforms that prohibit the execution of people who were children at the time of the crime. If the authorities wish any of those promises to be taken seriously, they should order an immediate halt to the planned execution of the seven, who were all children at the time of their arrest,” said Heba Morayef, Amnesty International’s Middle East and North Africa Director.
Saudi Arabia
Keywords: 2023-06 June

100 people executed as authorities continue relentless ‘killing spree’ - Amnesty International (Amnesty International, 2023)
Responding to the news that Saudi Arabia has already executed 100 people this year, Heba Morayef, Amnesty International’s Middle East and North Africa Director, said: “In clear contrast to Saudi Arabia’s repeated promises to limit its use of the death penalty, the Saudi authorities have already executed 100 people this year, revealing their chilling disregard for the right to life.
Saudi Arabia
Keywords: 2023-09 September

South Korea: Jail sentence for man who praised North an attack on freedom of expression - Amnesty International (Amnesty International, 2023)
Responding to the sentencing of a South Korean man, Lee Yoon-seop, to 14 months in prison for praising North Korea in a poem, Amnesty International’s East Asia Researcher Boram Jang said: “South Korean authorities must drop all charges against Lee Yoon-seop, who has been sentenced to jail simply for exercising his right to freedom of […]
Korea, Republic of
Keywords: 2023-10 November; Republic of Korea

What happened to Mahsa/Zhina Amini? - Amnesty International (Amnesty International, 2023)
In September 2022 Mahsa/Zhina Amini, a young woman from Iran’s oppressed Kurdish minority, visited Tehran with her brother. She was stopped and arrested by Iran’s “morality” police (gasht-e ershad), who routinely arbitrarily detain women who do not comply with the country’s abusive and discriminatory compulsory veiling laws.
Iran, Islamic Republic of
Keywords: 2023-09 September

Cambodia: Election takes place under cloud of human rights crisis - Amnesty International (Amnesty International, 2023)
The human rights situation in Cambodia has severely deteriorated since the last national election in 2018, Amnesty International’s interim Deputy Regional Director for Research Montse Ferrer said today, ahead of Sunday polls expected to be dominated by the ruling Cambodian People’s Party after the sole viable opposition group was blocked from participating. “Authorities in Cambodia have spent the past five years picking apart what’s left of the rights to freedom of expression, peaceful assembly and association. There is a growing crackdown on human rights in Cambodia. Many people feel that they are being forced to participate in this election despite their party of choice not being on the ballot.
Cambodia
Keywords: 2023-07 July; Government; Human Rights

TikTok’s ‘For You’ feed risks pushing children and young people towards harmful mental health content - Amnesty International (Amnesty International, 2023)
TikTok’s content recommender system and its invasive data collection practices pose a danger to young users of the platform by amplifying depressive and suicidal content that risk worsening existing mental health challenges.
Worldwide
Keywords: 2023-10 November

The authorities of Senegal must immediately halt the police violence and restore social media - Amnesty International (Amnesty International, 2023)
Reacting to the violence that broke out yesterday in Dakar and other towns following the verdict in the trial of opposition leader Ousmane Sonko, Samira Daoud, Amnesty International’s Regional Director for West and Central Africa
Senegal
Keywords: 2023-06 June

Arrest and detention of human rights lawyers an attack on the legal profession - Amnesty International (Amnesty International, 2023)
Amnesty International strongly condemns the arrest and detention of human rights lawyers simply for discharging their functions.
Zimbabwe
Keywords: 2023-09 September; Government

Argentina must investigate crimes against humanity committed by Venezuelan authorities - Amnesty International (Amnesty International, 2023)
The Clooney Foundation for Justice has filed a lawsuit in Argentina's federal courts.
Argentina
Keywords: 2023-06 June

In West and Central Africa, authorities must fight corruption and uphold the human rights of those who expose it - Amnesty International (Amnesty International, 2023)
West and Central African states must stop persecuting human rights defenders who expose corruption, bribery and abuse of office, and instead take concrete and effective measures to protect and support them, Amnesty International said today, in observing African Anti-Corruption Day. Today marks the 20th anniversary of the African Union Convention on Preventing and Combating Corruption.
Africa
Keywords: 2023-07 July; Human Rights Defenders; Middle Africa; Western Africa